Navigation tools for cellular automata in two families of tilings of the hyperbolic plane. Issue 1 (2nd January 2018) - Margenstern, Maurice
Abstract: This paper investigates two systems of coordinates for two infinite families of tilings of the hyperbolic plane. The systems have been used for the implementation of universal cellular automata on these tilings. Graphical Abstract: The figure illustrates a key property: the recursive construction of a bijection between a recursively generated tree and the tiling.